Natural History and Ecology of Interactions Between Bordetella Species and Amoeba - Ma, Longhuan; Linz, Bodo; Caulfield, Amanda D.; Dewan, Kalyan K.; Rivera, Israel; Harvill, Eric T. (Frontiers in Cellular and Infection Microbiology, 2022)
A variety of bacteria have evolved the ability to interact with environmental phagocytic predators such as amoebae, which may have facilitated their subsequent interactions with phagocytes in animal hosts. Our recent study found that the animal pathogen Bordetella bronchiseptica can evade predation by the common soil amoeba Dictyostelium discoideum, survive within, and hijack its complex life cycle as a propagation and dissemination vector. However, it is uncertain whether the mechanisms allowing interactions with predatory amoebae are conserved among Bordetella species, because divergence, evolution, and adaptation to different hosts and ecological niches was accompanied by acquisition and loss of many genes. Here we tested 9 diverse Bordetella species in three assays representing distinct aspects of their interactions with D. discoideum. Several human and animal pathogens retained the abilities to survive within single-celled amoeba, to inhibit amoebic plaque expansion, and to translocate with amoebae to the fruiting body and disseminate along with fruiting body. In contrast, these abilities were partly degraded for the bird pathogen B. avium, and for the human-restricted species B. pertussis and B. parapertussis. Interestingly, a different lineage of B. parapertussis only known to infect sheep retained the ability to interact with D. discoideum, demonstrating that these abilities were lost in multiple lineages independently, correlating with niche specialization and recent rapid genome decay apparently mediated by insertion sequences. B. petrii has been isolated sporadically from diverse human and environmental sources, has acquired insertion sequences, undergone genome decay and has also lost the ability to interact with amoebae, suggesting some specialization to some unknown niche. A genome-wide association study (GWAS) identified a set of genes that are potentially associated with the ability to interact with D. discoideum. These results suggest that massive gene loss associated with specialization of some Bordetella species to a closed life cycle in a particular host was repeatedly and independently accompanied by loss of the ability to interact with amoebae in an environmental niche.